Évolution de notre pratique de conception (1985-2005) - Yvon Haradji; Lydia Faveaux (Activités)
This text presents a historical vision of the evolution of our ergonomist practice in Human Computer Interaction, within a large industrial company. Based on user-centered design we have gradually established an explicit link between a human activity model and technical models in order to design new work situations or new everyday life situations. Using examples of projects resulting from our practice, we show that design, in terms of human activity assistance, can be structurally supported by interaction quality criteria like utility and usability. Modeling is presented as a means that is simultaneously able to reach quality criteria and to define the bases of structured cooperation between the different actors of design process (computer scientist, ergonomist...). Lastly, we have added a collective-work dimension to our problematic which has enabled us to distinguish fundamental interaction quality criteria (utility, usability…) from those which are transverse (accessibility, habitability…).